2020
DOI: 10.1021/acs.estlett.0c00740
|View full text |Cite
|
Sign up to set email alerts
|

Microplastics Mitigation in Sewage Sludge through Pyrolysis: The Role of Pyrolysis Temperature

Abstract: Sewage sludge is an important source of introducing microplastics into the environment, and thus, effective mitigation of microplastics in the sludge is in urgent need. Herein, the effect of pyrolysis on microplastics reduction in sewage sludge was investigated through a lab-scale study. The micro-Raman analysis showed that the microplastics concentrations in sludge residues decreased significantly from 550.8 to 960.9 particles/g to 1.4–2.3 particles/g with the pyrolysis temperature increasing to 500 °C, and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(36 citation statements)
references
References 47 publications
0
27
0
Order By: Relevance
“…Here, the condensate was water discharged from the GAC after thermal regeneration, such as pyrolysis. Previous studies on the pyrolysis of plastics contained in STP sludge reported that many polymers, such as PE, PP, PS, and PA, started to decompose at 375-500 • C [11,34]. However, it should be noted that there is no other study in the literature using GAC thermal regeneration for the removal of MPs.…”
Section: Effect Of Thermal Regeneration With Steammentioning
confidence: 99%
See 2 more Smart Citations
“…Here, the condensate was water discharged from the GAC after thermal regeneration, such as pyrolysis. Previous studies on the pyrolysis of plastics contained in STP sludge reported that many polymers, such as PE, PP, PS, and PA, started to decompose at 375-500 • C [11,34]. However, it should be noted that there is no other study in the literature using GAC thermal regeneration for the removal of MPs.…”
Section: Effect Of Thermal Regeneration With Steammentioning
confidence: 99%
“…The results indicate that the GAC thermal regeneration system could efficiently reduce MPs from the STP retrofitted with the GAC treatment process. Although existing studies on the removal of MPs from the GAC thermal regeneration system are rare, pyrolysis similar to GAC thermal regeneration systems is recognized as a promising sludge treatment technology for removing MPs in an STP [11]. For the removal of MPs in an STP, the major advantages of the GAC thermal regeneration system include the mechanism of filtering and pyrolysis.…”
Section: Mp Balance In the Suggested Treatment Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, effective plastic waste management and recycling should be promoted at community and jurisdictional levels. Mismanagement of plastic waste is considered a major cause of microplastic pollution (Ni et al 2020). It was estimated that only 9% of waste plastics were recycled by 2015 (Lambert and Wagner 2017).…”
Section: Perspectives and Solutionsmentioning
confidence: 99%
“…Microplastics (MPs) (particle size <5 mm) have been found in almost all environments on Earth, including urban centers, terrestrial areas, and freshwater environments as well as in remote uninhabited islands, deep seafloor, and polar regions (Liu et al 2019;Ni et al 2020;Yin et al 2021). They are released to the environment directly from primary sources (such as cosmetic and cleansing commodities, and personal care and pharmaceutical products), or indirectly from secondary sources through the fragmentation and degradation of meso and macroplastics (Schernewski et al 2020).…”
Section: Introductionmentioning
confidence: 99%